Pluralisme Hukum Dalam Bingkai Masyarakat Madani: Masa Nabi dan Masa Kini - Muhammadun Muhammadun (JURNAL INDO-ISLAMIKA, 2014)
In the era of modernization, law is no longer understood as a norm system that binds every citizen. In practice, the law is controlled and supervised by the state through a number of regulations created and compiled by certain communities that have direct access to the state. This paper will explore more about the concept of legal pluralism that once applied in the social history of Islamic law, as well as describing cases of legal pluralism that were practiced during the time of the Prophet and also friends.